2022
DOI: 10.3390/molecules27144505
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese Dalbergia tonkinensis: A Promising Source of Mono- and Bifunctional Vasodilators

Abstract: Hypertension is a risk factor for cardiovascular diseases, which are the main cause of morbidity and mortality in the world. In the search for new molecules capable of targeting KCa1.1 and CaV1.2 channels, the expression of which is altered in hypertension, the in vitro vascular effects of a series of flavonoids extracted from the heartwoods, roots, and leaves of Dalbergia tonkinensis Prain, widely used in traditional medicine, were assessed. Rat aorta rings, tail artery myocytes, and docking and molecular dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…LC-MS was used to investigate the possible correlation between the effect of L. paracasei and metabolism; the occurrence of diarrhea was related to intesti-nal microflora disruption. In this study, there are some antiinflammatory metabolites, such as dihydromyricetin, [63][64][65] and pinocembrin, [66][67][68][69] which were increased in the PE group, whereas dihydrokaempferol, 70,71 pinocembrin, dihydromyricetin, and rimexolone, which can inhibit CD4 + T cells, 72 were reduced in the CIP group. The results suggest that L. paracasei can promote the production of anti-inflammatory substances.…”
Section: Papermentioning
confidence: 66%
“…LC-MS was used to investigate the possible correlation between the effect of L. paracasei and metabolism; the occurrence of diarrhea was related to intesti-nal microflora disruption. In this study, there are some antiinflammatory metabolites, such as dihydromyricetin, [63][64][65] and pinocembrin, [66][67][68][69] which were increased in the PE group, whereas dihydrokaempferol, 70,71 pinocembrin, dihydromyricetin, and rimexolone, which can inhibit CD4 + T cells, 72 were reduced in the CIP group. The results suggest that L. paracasei can promote the production of anti-inflammatory substances.…”
Section: Papermentioning
confidence: 66%
“…Additional hydrogen bond interactions were formed with Leu774 and Ala1183. Intriguingly, the flavanone gave rise to a π-π stacking interaction with the Phe1190 side ring instead of the closer Phe778, diverging from other flavonoids [19]. Ala1183 and Phe1190 residues are highly conserved in the Ca V 1.2 channel α 1C subunit across species, warranting site-directed mutagenesis experiments to determine their relevance in (2S)-sakuranetin blockade of Ca V 1.2 channels.…”
Section: Discussionmentioning
confidence: 98%
“…Phytochemical studies of the genus Dalbergia have indicated that its chemical constituents are various flavonoids as flavones, isoflavones, neoflavones, flavanones, isoflavanones, flavanes, isoflavanes, neoflavans, 4-arylcoumarins, phenols, sesquiterpenes, phytosterols, together coumaronochromone derivatives [6,7,8] The Dalbergia tonkinensis Prain species (commonly called 'Sua Do'), is a medium-size floral species 5-13 meters, is widely distributed scattered from North to Sonth in Vietnam and is classified as precious tree species listed in the Red Book.This is rare spices with high valuable economic [ and neoflavonoid were isolated [5,6]. In this paper, we describle the isolate and structural elucidation of two compounds, sativanone (1), and 3'-O-methylviolanone (2) from the wood of this species.…”
Section: Introductionmentioning
confidence: 99%
“…Various biological activities of the Dalbergia species have reported, including antimicrobial, antidiarrheal, anti-cancer, spermicidal, anti-inflammatory, antipyretic, analgesic, and cardiovascular activity [5]. In addition.…”
Section: Introductionmentioning
confidence: 99%